ROLE OF THE YOUTH INFORMATION AND COUNSELING CENTER (PIK-R) IN FORMING ADOLESCENT SELF-CONCEPT THROUGH LUDRUK ART - Shafa Fedha (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
Adolescence is one of the most dynamic and complex phases of human development. In this case, the self-concept of adolescents needs to be prepared and developed. One of them is through the Youth Information and Counseling Center (PIK-R). PIK-R Elixir is one of the PIK-Rs located in Kapasari Village, Genteng District, Surabaya City. PIK-R Elixir is not only socialization activities, but in PIK-R Elixir there are several activities, one of which is LAK (Ludruk Arek Kapasari). LAK is an innovation from PIK-R related to how they socialize the issues experienced by adolescents in the form of a role through the art of ludruk. The purpose of this research is to find out how the role of PIK-R in the formation of adolescent self-concept through ludruk art. This study is a qualitative research involving 3 participants. Data were obtained through in-depth interviews. The result of this study is that the existence of ludruk art is one of the media that can support the process of self-concept formation